SHARIA STOCK INDEX AND POST COVID-19 PANDEMIC: WHAT DOES THE CAPM MODEL TELL US? - Randy Kuswanto (FEB-UP Press, 2022)
The aftermath of COVID-19 pandemic has had a major impact on the economic sector, especially the capital market. However, the process of economic recovery took place quite quickly, entering 2021. This study aims to investigate the performance of the Jakarta Islamic Index (JII) stock index, which has not recovered throughout 2021. This research is quantitative descriptive with a sample of 30 stocks listed on the JII index. The analysis technique uses the CAPM model to evaluate and classify stocks on the JII index. The study results show that Islamic stocks listed on the JII index have a negative expected performance throughout 2021. This finding makes the JII index stocks are not recommended as a stock portfolio. The CAPM model also identifies 20 JII index stocks as efficient short-term investments during economic recovery. Furthermore, Islamic stocks tend to be riskier during the economic recovery period after the COVID-19 pandemic.